Pengaruh Metode Proyek Pembuatan Susu Kedelai Terhadap Keterampilan Proses Sains Anak Di Taman Kanak-Kanak Kartika 1-63 Padang - Husna, Wildatul; Yaswinda, Yaswinda (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
Science learning is meaningful as a learning process that is directly related to the child's environment. Children can explore directly what they find. One of the implementation of learning to improve children's science process skills is to use science learning using the soy milk project method in learning. This study aims to determine the effect of the soy milk production project method on children's processing skills. The population is all students in Kindergarten Kartika 1-63 Padang City for the 2023/2024 academic year. The samples in this study were B1 18 (experimental) and B2 (control). The data collected is the child's science process skills during the experiment. The results obtained are that there is a significant effect of the use of the project method on the process skills of children in Kindergarten Kartika Padang